Fransk litteratur i Sverige 1830–1900: Översättning, reception och spridning - Mörte Alling, Annika (Tidskrift för litteraturvetenskap, 2010)
French Literature in Sweden 1830–1900. Translation, Reception and Circulation The article presents some results from an international project on the introduction of French literature in Scandinavia during the 19th century. A point of departure is the database BREFS (Bibliographie du Réalisme Français en Scandinavie), containing the translations of novels, short stories, poetic works and theatre plays that were published in Denmark, Finland, Iceland, Norway and Sweden in book form from 1830 to 1900. The Swedish part of the bibliography is in focus, consisting of as many as 1 500 translations, and a list of the seemingly most popular French writers in Sweden during the period is presented. With some exceptions, these writers are probably unknown to most Swedes, and not even mentioned in historical surveys of Swedish literature: Eugène Scribe, Eugène Sue, Charles Perrault, Anne H. J. Duveyrier, Henri Meilhac, Olivier Gloux, Michel Carré, Alice Durand and Jean F. A. Bayard. In fact, when it comes to the number or translations published, these authors by far exceed the wellknown representations of the French realist period, Stendhal, Balzac, Flaubert and Maupassant. I try, briefly, to relate these results to research that has been done by others on translation in the nineteenth century, the working conditions of the translators, the reception of French authors and the role of French theatre in Sweden, which was so successful at the time.